Alternative Seedling Media Using Dicranopteris linearis and Rice Husk Charcoal for Acacia mangium - Astuti, Ria; Pamoengkas, Prijanto; Srena, Mona Fhitri; Zuhriansah, Alfi Laila; Rahmah, Hanifa; Kusuma, Yosie Syadza; Br Lubis, Rizky Febriana (Jurnal Biologi Tropis, 2025)
Seedling quality contributes significantly to the development of industrial forest plantations. This study assessed Dicranopteris linearis (Resam) and rice husk charcoal mixtures as an alternative nursery media for Acacia mangium Willd. seedlings. The study was carried out using a Completely Randomized Design, and the data were analyzed using ANOVA. Five mixtures of resam and rice husk charcoal were tested: A (100% control), B (80%:20%), C (70%:30%), D (60%:40%), and E (50%:50%). The ratio of 70%:30% yielded the best performance, with a mean height of 12.84 cm, fresh weight of 4.63 grams, dry shoot weight of 1.53 grams, and a Seedling Quality Index (SQI) of 0.0018. These findings highlight mixed media C as the most effective composition and confirm the potential of resam and rice husk charcoal mixture as an effective and sustainable nursery media for industrial forest plantation.